Deen al-Fitrah (Primordial religion): nurturing inter-religious dialogue and beyond in al-Faruqi’s thoughts - Shehu, Fatmir Mehdi (Peeters Publishers, 2018)
The goal of this paper is to(Primordial religion): nurturing inter-religious dialogue and beyond in al-Faruqi’s thoughts expound the spiritual basis of inter-religious dialogue by revisiting the writings of Ismail Raji al-Faruqi. This research will investigate al-Faruqi’s thoughts on Dīn al-Fiṭrah (Primordial Religion), from a spiritual basis and as a religious norm that nurtures inter-religious dialogue and beyond between the adherents of three revealed religions, Judaism, Christianity, and Islam. The topics dealt with are: (1) al-Faruqi’s thoughts on Dīn al-Fiṭrah (Primordial Religion), (2) al-Faruqi’s views on inter-religious dialogue, and (3) al-Faruqi’s stance on nurturing inter-religious dialogue and beyond in light of Dīn al-Fiṭrah (Primordial Religion). This paper employs descriptive and analytical methods as well as critical method. The findings of this study enrich the perspective of modern comparative religious studies with insights into the original efforts of al-Faruqi towards the notion of inter-religious dialogue.